Asked by ishmeet kaur Sidana | 21st Jul, 2013, 03:57: PM
Please cross check the polynomial should have the constant term as +7 instead of -7.
Divide the polynomial x^3-3x^2+3x+7 by (x+1).
You will get 0 as the remainder and x^2 - 4x + 7 as the quotient.
So, x^3-3x^2+3x-7=(x+1)(x^2 - 4x + 7)
Thus, on comparing the quotient with (ax^2+bx+c), we get, a = 1, b = -4 and c = 7
Thus, a + b + c = 4
Answered by | 21st Jul, 2013, 04:04: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number